Pengaruh Virtual Influencer dan Brand Attitude terhadap Purchase Intention pada Kampanye BMW iX2 × Lil Miquela (STUDI PADA MAHASISWA FISIP USU) - Manzilatul Nafla; Nathania Anggini Hutabarat; Theresa Melyasari Br Simatupang; Lianti Hafni Saragih; Rachel Aurel Saragih; Hage Hanyta Sembiring; Onan Marakali Siregar; Ummi Salamah Sitorus (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2026)
The rapid advancement of artificial intelligence (AI) technology has given rise to the phenomenon of virtual influencers, which are now increasingly being utilized in contemporary digital marketing strategies, specifically to promote global-scale innovative products. This study aims to explain and analyze in-depth the influence of Virtual Influencers and Brand Attitude on Future Purchase Intention in the collaborative marketing campaign of BMW iX2 × Lil Miquela. This study applies an explanatory quantitative approach using a survey method. Sampling was conducted using a purposive sampling technique on 126 active students of the Faculty of Social and Political Sciences, Universitas Sumatera Utara. The respondent characteristics focused on the digital native generation who are familiar with the virtual influencer entity Lil Miquela and understand the profile of the luxury automotive brand BMW. These empirical findings explicitly indicate that although the visual appeal and interaction of a virtual influencer can effectively stimulate the cognitive attention of young audiences, brand attitude remains the most dominant predictor in driving consumer behavioral intentions. In conclusion, the high credibility and historical reputation of the luxury brand BMW have proven to be the main foundation for Generation Z when considering the adoption of cutting-edge automotive products in the future.